Effective tax rates of MNEs New evidence on global low-taxed profit - Hugger, Felix (OECD Taxation Working Papers, 2023)
The effective taxation of corporate profits is at the centre of an active public and academic debate. This debate is often focused on the extent of low-taxed profit of multinational enterprises (MNEs) in jurisdictions with low statutory tax rates or low average effective tax rates (ETRs). However, some affiliates in high tax jurisdictions may also be subject to low ETRs, due to tax incentives or other provisions. To date, a global accounting of the ETRs paid by MNEs that incorporates within-country heterogeneity has been missing. Using a new dataset on the global activities of large MNEs, this paper provides new estimates of the distribution of effective tax rates of large MNEs across and within jurisdictions. The results show that low tax profit is common, and that substantial low-taxed profit exists outside low tax jurisdictions. We estimate that high tax jurisdictions (jurisdictions with average ETRs of above 15%) account for more than half (53.2%) of global profits taxed below 15%, much more than very low tax jurisdictions (those with average ETRs below 5%) which only account for 18.7% of low-taxed profits. This suggests that an assessment of global low-taxed profit that focuses only on jurisdictions with low average ETRs could potentially miss out on more than half of global low-taxed profit